Screening And Education On Prevention Of Degenerative Diseases in Coastal Communities in Panjang Island, Batam - Fifin Oktaviani; Heldi Candra; Hilda Muliana (International Journal of Health and Social Behavior, 2025)
The screening and education program on the prevention of degenerative diseases was conducted in the coastal community of Panjang Island, Batam. This initiative aimed to address the high prevalence of degenerative diseases such as diabetes, hypertension, and dyslipidemia through health screenings and community education. The study involved 55 participants, primarily pre-elderly individuals, and included examinations of blood pressure, cholesterol, blood sugar, and uric acid. The results revealed that 65.5% of participants had hypertension (34.5% with Stage 1 and 31% with Stage 2), while 69.1% had high cholesterol levels. Blood sugar screening indicated that 14.5% of participants had elevated glucose levels. Uric acid levels were high in 47.3% of participants, predominantly among women. Additionally, 78% of respondents with comorbidities presented abnormalities in at least one biochemical parameter. Educational sessions resulted in a 26.4% increase in knowledge about disease prevention and healthy lifestyles. The program highlighted the importance of regular health screenings, lifestyle modifications, and community empowerment for sustainable health improvements. Collaboration with local health centers and the establishment of health cadres are recommended for ongoing support and monitoring of degenerative disease prevention efforts.